DECONTAMINATION OF HARMFUL HEAVY METALS IN SOILS USING AGRO-ORES AND HUMATES - Boynazarov Baxron Raimovich; Usanboyev Najmiddin Khalmirzayevich; Khudayarov Makhmasaid Makhmarajabovich (American Journal of Biodiversity, 2024)
The article presents the results of determining the total and soluble forms of heavy metals in industrial soils. It was found that the addition of potassium humate and natural bentonite clay isolated from coal oxidized in a solution of H2O2 to soils contaminated with heavy metals significantly reduces the soluble forms of heavy metals.